Physical Activity Level and Quality of Life of Children Treated for Malignancy, Depending on Their Place of Residence: Poland vs. the Czech Republic: An Observational Study - Kowaluk, Aleksandra; Siewierska, Katarzyna; Choniawkova, Marie; Sedlacek, Petr; Kałwak, Krzysztof; Malicka, Iwona (Cancers, 2023)
This study aimed to assess the level of physical activity (PA) and quality of life of cancer-treated children, depending on their place of residence (Poland vs. the Czech Republic, where incidence and mortality rates of childhood malignancies are similar). A total of 68 school-age children (7-18 years) undergoing oncological treatment were included in this study. This study used the quality of life questionnaire (KIDSCREEN-10) and the HBSC questionnaire. This study showed statistically significant differences in the level of PA between Polish and Czech children. In Poland, 93.75% of children exhibited no weekly physical effort at the level of moderate to vigorous PA. In the Czech Republic, 69.44% of children engaged in PA lasting at least 60 min per day, or at least 1 day weekly. Physically active children engaging in more frequent effort, at least 60 min daily, reported higher physical performance (rho = 0.41), higher energy levels (rho = 0.41), and less mood disturbance (rho = -0.31). Children with good relationships with parents were more likely to engage in submaximal PA and spend less time on stationary games. Our study showed that an appropriate level of PA improves well-being and quality of life. It is crucial to promote attractive PA programs tailored for cancer-treated children.
Keywords: paediatrics patients; quality of life; physical activity; oncology; children